Congenital heart disease in adults and its problems - Teddy Ontoseno (Indonesian Pediatric Society, 2001)
There were 40 adult congenital heart disease (CHD) patients seen in the Cardiology Division during 1 year (February 1993 - February 1994). The most frequently seen defect was atrial septal defect; however there were also cases with patent ductus arteriosus, pulmonary stenosis, ventricular septal defect, and tetralogy of Fallot. Hemodynamic disorder, serious hindrance to education achievement, and occupational threat due to limited physical capabilities as well as malnutrition are some of prominent issues to be closely anticipated. In general the older the patients the more serious hemodynamic disorder they suffer due CHD. It is worth thinking how to improve the quality of life of CHD patients who succeed to live their adult lives and minimize any possible fatal complication risks.